A Unique Case of Complex Interaction Between MSTIDs and Mid‐Latitude Field‐Aligned Plasma Depletions Over Geomagnetic Low‐Mid Latitude Transition Region. Issue 1 (31st December 2020) - Yadav, V.; Rathi, R.; Sarkhel, S.; Chakrabarty, D.; Sunil Krishna, M. V.; Upadhayaya, A. K.
Abstract: On a geomagnetically quiet night of July 07, 2018, the allsky imager at Hanle, Leh Ladakh (32.7°N, 78.9°E; Mlat. ∼24.1°N), India captured a number of plasma structures in O ( 1 D) 630.0 nm airglow emission. In a short observational period of around 3 h, two different medium scale traveling ionospheric disturbances and two different mid‐latitude plasma depletions were observed. The most interesting aspect of the night was the drastic difference in the behavior of the two plasma depletions, which simultaneously existed within the imager's field of view for a long time. One of the plasma depletions, which we have termed as mid‐latitude field‐aligned plasma depletion, was nearly field aligned, drifted westward very slowly and became more prominent later in the night. The other depletion showed a much more ambiguous behavior with large reduction in its drift as well as significant change in its orientation relative to the geomagnetic meridian. In the present study, we have tried to explain this contrasting behavior in two different scenarios and have discussed arguments supporting each scenario along with their limitations. These observations are particularly useful considering the location of Hanle, which lies at a transition of geomagnetically low‐mid latitudes, which are governed by different electrodynamics. Key Points: Two medium scale traveling ionospheric disturbances (MSTIDs) structures and a couple of complex plasma structures are observed in a span of ∼3 h over Hanle One of the plasma structures exhibits ambiguous behavior where it is an extended part of the first MSTID or an independent plasma bubble The second plasma structure appears to be a fossil bubble